Understanding the adoption of Pay-for-performance in state governments: A diffusion theory approach - Sangyub RYU; John C. RONQUILLO; Seejeen PARK (Transylvanian Review of Administrative Sciences, 2018)
As various private sector practices have been introduced into the public sector, some were adopted without careful assessment of potential policy and management implications. One such example is the adoption of pay-for-performance (PFP). While previous research has corroborated that this performance incentive mechanism was implemented without thorough assessment, the diffusion process of PFP has not been empirically tested or evaluated. This study applies a regional diffusion model among American (U.S.) states to examine the diffusion process. Findings show that state governments tend to adopt PFP plans when they become aware of their neighbouring states adopting them, but the marginal probability of adoption decreases as the numbers of neighbours adopting such plans